2019
DOI: 10.3390/cancers12010057
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Breaks Tumor Immune Tolerance by Downregulating Tumor Programmed Death-Ligand 1 Expression

Abstract: Immunotherapy is becoming a popular treatment modality in combat against cancer, one of the world’s leading health problems. While tumor cells influence host immunity via expressing immune inhibitory signaling proteins, some bacteria possess immunomodulatory activities that counter the symptoms of tumors. The accumulation of Salmonella in tumor sites influences tumor protein expression, resulting in T cell infiltration. However, the molecular mechanism by which Salmonella activates T cells remains elusive. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The growth rate of tumor might be a critical factor involved Salmonella treatment. Furthermore, we have demonstrated that Salmonella can inhibit tumor growth in tumor-bearing mice [14,17]. We investigate the possible mechanism causing the regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth rate of tumor might be a critical factor involved Salmonella treatment. Furthermore, we have demonstrated that Salmonella can inhibit tumor growth in tumor-bearing mice [14,17]. We investigate the possible mechanism causing the regression.…”
Section: Discussionmentioning
confidence: 99%
“…choleraesuis (Smith) Weldin serovar Dublin (ATCC 15480)] was obtained from Bioresources Collection and Research Center (Hsinchu, Taiwan) [13]. As described above, a constitutively active AKT plasmid were used in this study [14][15][16]. The resveratrol and 4',6-Diamidino-2-Phenylindole (DAPI) a were purchased from Sigma-Aldrich (Sigma Aldrich, St. Louis, MO, USA).…”
Section: Cells Bacteria Plasmids Reagents and Animalsmentioning
confidence: 99%
“…Data from these experiments demonstrated that Salmonella downregulated PD-L1 expression in a p-AKT, p-mTOR and p-p70S6K involved manner. As a result of reduced apoptosis, the T cell numbers rose ( 79 ). Salmonella also affects other immunosuppressive cells ( 60 ) in the TME.…”
Section: Salmonella In Cancer Therapymentioning
confidence: 99%
“…Among them, the relationship between Salmonella and immune checkpoint has not received sufficient attention. Chen et al found the down-regulation of PD-L1 expression in a variety of mouse and human tumor cells treated with Salmonella , affects apoptosis of co-cultured PD-1-expression cells ( 79 ). However, PD-L1 is also expressed in other non-tumor cells in TME, such as stromal cells, myeloid-derived cells and infiltrating immune cells ( 169 , 175 ).…”
Section: Integration Of Salmonella Into Combination Immunotherapymentioning
confidence: 99%
“…Third, the lack of major histocompatibility complex class I on the surface of tumor cells can lead to the inability of the immune recognition of CD8+ cytotoxic T cells to mediate immune tolerance (63). In addition, upregulated expression of immunosuppressive ligands, such as programmed cell death-ligand 1, also mediates tumor immune tolerance (64). Subsequently, the immune cells in both innate and adaptive immunity become apoptotic due to the lack of stimulation of tumor-associated antigens and the inability to specifically recognize tumor cells, leading to the immune escape of tumors (65,66).…”
Section: The Tumor Immunosuppressive Environmentmentioning
confidence: 99%